Pilot study of Creating Change, a new past‐focused model for PTSD and substance abuse. (15th March 2014) - Najavits, Lisa M.; Johnson, Kay M.
<x xml:space="preserve">Abstract</x> Background and Objectives Creating Change (CC) is a new past‐focused behavioral therapy model developed for comorbid posttraumatic stress disorder (PTSD) and substance use disorder (SUD). It was designed to address current gaps in the field, including the need for a past‐focused PTSD/SUD model that has flexibility, can work with complex clients, responds to the staffing and resource limitations of SUD and other community‐based treatment programs, can be conducted in group or individual format, and engages clients and clinicians. It was designed to follow the style, tone, and format of Seeking Safety, a successful present‐focused PTSD/SUD model. CC can be used in conjunction with SS and/or other models if desired. Methods We conducted a pilot outcome trial of the model with seven men and women outpatients diagnosed with current PTSD and SUD, who were predominantly minority and low‐income, with chronic PTSD and SUD. Assessments were conducted pre‐ and post‐treatment. Results Significant improvements were found in multiple domains including some PTSD and trauma‐related symptoms (eg, dissociation, anxiety, depression, and sexual problems); broader psychopathology (eg, paranoia, psychotic symptoms, obsessive symptoms, and interpersonal sensitivity); daily life functioning; cognitions related to PTSD; coping strategies; and suicidal ideation (altogether 19 variables, far exceeding the rate expected by chance). Effect sizes were consistently large, including for both alcohol and drug problems. No adverse events were reported. Discussion and Conclusions Despite study methodology limitations, CC is promising. Scientific Significance Clients can benefit from past‐focused therapy that addresses PTSD and SUD in integrated fashion. (Am J Addict 2014;23:415–422)